USING GUESSING GAMES TO IMPROVE STUDENTS’ SPEAKING SKILL - Ni Putu Widiari Kusuma Dewi; Putu Ayu Paramita Dharmayanti; I Nengah Astawa (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
The study aims at figuring out whether or not the speaking skill at the eighth grade students of SMPN 1 Kuta Utara in academic year 2019/2020 can be improved through the implementation of Guessing Games.The subjects were the eighth grade students of SMPN 1 Kuta Utara.There were 36 subjects which consist of 12 females and 24 males.The design was classroom action research design. The research was carried out through implementing Guessing Games in two cycles and the obtained data was analyzed quantitively from the pre-test, post-test 1 and post-test 2; then qualitatively from the questionnaire. The result showed that the students’ mean score had significant improvement from the pre-test was 49.72 to 64.86 in post-test 1, and 75.69 in post-test 2. Furthermore, to collect the additional supporting data; the researcher administered the questionnaire at the end of cycle II. It showed that the students responded positively and it could be seen that the result of the questionnaire showed the percentage of 60.68% Sangat Setuju/SS (strongly agreed) with the implementation of Guessing Games in improving speaking skill.